What motivates people with substance use disorders to pursue treatment? A patient-centered approach to understanding patient experiences and patient-provider interactions. (2nd November 2019) - Gressler, L. E.; Natafgi, N. M.; DeForge, B.; Shaneman-Robinson, B.; Welsh, C.; Shaya, Fadia
ABSTRACT: Objectives: To identify and define potential positive and negative factors in patient experiences and patient-provider interactions that are associated with the pursuit and maintenance of treatment by those suffering from substance use disorders (SUD). Methods: Two focus groups with patients in treatment for SUD were performed. The focus groups focused on questions aimed at mapping factors associated with initiating and maintaining treatment along the transtheoretical model of change. Four in-depth interviews with healthcare providers involved in the treatment of patients with SUD were also conducted to understand providers' perspective on similar factors. Results: Fourteen patients were included in the focus groups. Patients identified their life prior to treatment as chaotic and further identified internal and external factors that influenced seeking treatment. The four healthcare providers identified primarily social issues such as lack of housing as an external barrier. Both patients and providers cited the importance of a trusting and empathetic relationship between the patient and providers, as well as the patient's willingness to change as primary motivating factors for the initiation and maintenance of treatment. Conclusions: From a patient and provider perspective, facilitators and barriers for initiating and maintaining may vary by person and are multifactorial.